2009
DOI: 10.1158/1535-7163.mct-08-0964
|View full text |Cite
|
Sign up to set email alerts
|

SHP and Sin3A expression are essential for adamantyl-substituted retinoid-related molecule–mediated nuclear factor-κB activation, c-Fos/c-Jun expression, and cellular apoptosis

Abstract: We previously found that the adamantyl-substituted retinoid-related molecules bind to the small heterodimer partner (SHP) as well as the Sin3A complex. In this report, we delineated the role of SHP and the Sin3A complex in 4-[3′-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…We show that ING2 sumoylation enhances its association with Sin3A. Sin3A is a stable component of the Sin3A/HDAC chromatin-modifying complex and is thus involved not only in the repression but also in the activation of a large number of genes (Dannenberg et al, 2005;Farhana et al, 2009). ING2 and Sin3A were previously shown to associate to regulate gene expressions (Shi et al, 2006).…”
Section: Ing2 Sumoylation and Sin3a Mediate Gene Expressionmentioning
confidence: 87%
“…We show that ING2 sumoylation enhances its association with Sin3A. Sin3A is a stable component of the Sin3A/HDAC chromatin-modifying complex and is thus involved not only in the repression but also in the activation of a large number of genes (Dannenberg et al, 2005;Farhana et al, 2009). ING2 and Sin3A were previously shown to associate to regulate gene expressions (Shi et al, 2006).…”
Section: Ing2 Sumoylation and Sin3a Mediate Gene Expressionmentioning
confidence: 87%
“…Although ARRs were initially synthesized to demonstrate selectivity in the activation of retinoid nuclear receptor (RAR) subtypes, they have been shown to inhibit growth and induce apoptosis in different malignant cell types independent of RAR and retinoid x receptor (RXR) activation and function [3034]. We found that Ras wild type and mutant pancreatic cancer cell lines COLO357, PANC-1, Capan-2, AsPc-1 cells, and MiaPaCa-2 display significant sensitivity to AHP3- and 3-Cl-AHPC-mediated growth inhibition and apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the ARRs to enhance or inhibit the expression of a number of genes and proteins has been demonstrated [3035]. We have found that both 3-Cl-AHPC and AHP3 significantly decreased IGF-1R and β -catenin expression and that the decreased expression of IGF-1R and β -catenin inhibited the growth and enhanced apoptosis of the pancreatic cancer cells suggesting that decreased IGF-1R and β -catenin expression potentiates ARR-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the loss of SHP or Sin3A expression had little effect on ARR inhibition of cellular proliferation, suggesting that ARR mediated growth inhibition and apoptosis seem to involve separate pathways [48]. Continued study showed that induction of c-Fos and c-Jun expression as well as NF-kappaB activation by ARRs were SHP-dependent and may be essential for ARR mediated apoptosis [45]. A more recent in vivo and in vitro study found that the human acute myelogenous leukemia cell line FFMA-AML and TF (v-SRC) cells displayed resistance to standard retinoid (including trans-retinoic acid, 9-cis-retinoic acid, and the synthetic retinoid TTNPB) induced apoptosis but showed sensitivity to 3-Cl-AHPC and AHPN mediated apoptosis.…”
Section: Shp and Apoptosismentioning
confidence: 99%